2004
DOI: 10.2337/diabetes.53.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Content Is Increased in Skeletal Muscle From Obese Insulin-Resistant Humans

Abstract: Increased intramyocellular lipid concentrations are thought to play a role in insulin resistance, but the precise nature of the lipid species that produce insulin resistance in human muscle are unknown. Ceramides, either generated via activation of sphingomyelinase or produced by de novo synthesis, induce insulin resistance in cultured cells by inhibitory effects on insulin signaling. The present study was undertaken to determine whether ceramides or other sphingolipids are increased in muscle from obese insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
453
7
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 578 publications
(499 citation statements)
references
References 42 publications
30
453
7
6
Order By: Relevance
“…This observation is consistent with our results in a previous study on young male untrained and endurance-trained participants, presumably having different insulin sensitivities, in which muscle ceramide content was similar in the resting overnight fasted condition [14]. As mentioned above, our finding is in contrast to two studies that found higher muscle ceramide content in young obese insulinresistant participants compared with lean controls [11,12]. This discrepancy could be explained by the presence of an increased muscle ceramide concentration in obese individuals.…”
Section: Basalsupporting
confidence: 92%
See 3 more Smart Citations
“…This observation is consistent with our results in a previous study on young male untrained and endurance-trained participants, presumably having different insulin sensitivities, in which muscle ceramide content was similar in the resting overnight fasted condition [14]. As mentioned above, our finding is in contrast to two studies that found higher muscle ceramide content in young obese insulinresistant participants compared with lean controls [11,12]. This discrepancy could be explained by the presence of an increased muscle ceramide concentration in obese individuals.…”
Section: Basalsupporting
confidence: 92%
“…Effect of insulin on muscle ceramide content In the present study, muscle ceramide content was not influenced by stimulation with low or high insulin levels during the clamp, which is consistent with prior observations showing no effect of insulin on muscle ceramide content in human skeletal muscle [11,15,16]. Muscle ceramides are generated primarily through de novo synthesis from palmitate and serine, or through the breakdown of sphingomyelin in the membranes [22,28,29].…”
Section: Basalsupporting
confidence: 91%
See 2 more Smart Citations
“…More recent insights from various lipid infusion studies have led to an alternative mechanism [9][10][11][12][13]. The latter suggests that elevated NEFA delivery and/or impaired FA oxidation result in intramyocellular accumulation of triacylglycerol (TG) and FA metabolites (such as fatty acyl-CoA, ceramides and diacylglycerol), which induce defects in the insulin signalling cascade, causing skeletal muscle insulin resistance [9,10,[13][14][15][16][17]. Insulin resistance can subsequently lead to development of the hyperglycaemic and/or hyperinsulinaemic state that is associated with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%